Use of physical restraint procedures in educational settings: recommendations for educators. Issue 3 (5th July 2022) - Kern, Lee; Mathur, Sarup R.; Peterson, Reece
Abstract: The Division for Emotional and Behavioral Health (DEBH; Formerly Council for Children with Behavioral Disorders, CCBD) put forward a position paper with recommendations for the use of physical restraint procedures in educational settings. In addition to providing relevant background regarding the use of restraint, the position paper set forth a Declaration of Principles and offered specific recommendations for its use. The current paper follows up on CCBD's position paper, elaborating on the specific recommendations as they pertain to practitioners and administrators who serve children with behavioral challenges.